Inhibition of Cytochrome P450 Side-Chain Cleavage Attenuates the Development of Mechanical Allodynia by Reducing Spinal D-Serine Production in a Murine Model of Neuropathic Pain - Choi, Sheu-Ran; Beitz, Alvin J.; Lee, Jang-Hern (Frontiers in Pharmacology, 2019)
Research indicates that neurosteroids are locally synthesized in the central nervous system and play an important modulatory role in nociception. While the neurosteroidogenic enzyme, cytochrome P450 side-chain cleavage enzyme (P450scc) is the initiating enzyme of steroidogenesis, P450scc has not been examined under the pathophysiological conditions associated with peripheral neuropathy. Thus, we investigated whether chronic constriction injury (CCI) of the sciatic nerve increases the expression of P450scc in the spinal cord and whether this increase modulates serine racemase (Srr) expression and D-serine production contributing to the development of neuropathic pain. CCI increased the immunoreactivity of P450scc in astrocytes of the ipsilateral lumbar spinal cord dorsal horn. Intrathecal administration of the P450scc inhibitor, aminoglutethimide during the induction phase of neuropathic pain (days 0 to 3 post-surgery) significantly suppressed the CCI-induced development of mechanical allodynia and thermal hyperalgesia, the increased expression of astrocyte Srr in both the total and cytosol levels, and the increases in D-serine-immunoreactivity at day 3 post-surgery. By contrast, intrathecal administration of aminoglutethimide during the maintenance phase of pain (days 14 to 17 post-surgery) had no effect on the developed neuropathic pain nor the expression of spinal Srr and D-serine-immunoreactivity at day 17 post-surgery. Intrathecal administration of exogenous D-serine during the induction phase of neuropathic pain (days 0 to 3 post-surgery) restored the development of mechanical allodynia, but not the thermal hyperalgesia, that were suppressed by aminoglutethimide administration. Collectively these results demonstrate that spinal P450scc increases the expression of astrocyte Srr and D-serine production, ultimately contributing to the development of mechanical allodynia induced by peripheral nerve injury.